MARKETING MENTAL WELLNESS TO GEN Z: A CASE STUDY OF UNDERSTANDING BEHAVIORAL INTENTIONS TOWARD DIGITAL MENTAL HEALTH APP - Mochammad Riyadh Rizky Adam; Oyyappan Duraipandi; Derek Ong Lai Teik (Veredas do Direito, 2026)
This study aims to examine Generation Z’s behavioral intentions regarding the use of a mental health app. This study adopts the technology acceptance model (TAM) and signaling theory to analyze the factors that influence Gen Z’s propensity to adopt digital mental health solutions in the context of parent-child relationship issues that affect their mental health. The research investigates the relationships between perceived usefulness, perceived ease of use, brand competence, attitude toward using a mental health app, and behavioral intention to use these digital services. A quantitative cross-sectional study was conducted with 311 Generation Z participants (aged 18-25) in Jakarta and surrounding urban areas who reported parent-child relationship issues affecting their mental health. Data were collected through online questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) in SmartPLS. The measurement model was evaluated for validity and reliability, followed by structural model testing for hypothesis testing and goodness of fit analysis. The findings reveal that perceived usefulness and attitude directly influence behavioral intention to use a mental health app. While perceived ease of use influenced perceived usefulness, it did not directly affect attitude or intention. Interestingly, brand competence negatively influenced behavioral intention, suggesting worriedness toward brand-driven signals in mental health contexts among Generation Z. The model demonstrated strong validity and moderate predictive power. This study fills a gap in the literature by integrating branding signals into technology acceptance models within the mental health domain. It offers novel insights into how young, urban digital natives in Indonesia cognitively and emotionally engage with digital wellness platforms when confronting family-driven stress. The findings guide app developers, marketers, and mental health providers on designing authentic, value-driven interventions that resonate with Gen Z users.